ARTISANAL FISHING ON THE COAST OF ESPÍRITO SANTO STATE, SOUTHEASTERN BRAZIL: AN APPROACH TO SOCIOENVIRONMENTAL OCEANOGRAPHY - Joelson MUSIELLO-FERNANDES; Pablo da Costa OLIVEIRA; Samanta Chisté de ARAÚJO; Juliana Silva de ABREU; Ana Paula Madeira DI BENEDITTO; Adriane Araújo BRAGA; Mauricio HOSTIM-SILVA; Camilah Antunes ZAPPES (Boletim do Instituto de Pesca)
Artisanal fishing is an important traditional activity on the coast of Espírito Santo (ES) State, southeastern Brazil. Despite this, there is a lack of updated data on artisanal fishing and its interfaces with socioenvironmental oceanography. The present study describes the social profile of fishers (gender, age, education, and period of professional activity) and the fishing activity (fishing gear and target species) along the coast of Espírito Santo State. Interviews with semi-structured questionnaires were carried out with 366 artisanal fishers living in 10 fishing communities. The interviewed fishers are mostly male, with low education, who had been fishing for more than 41 years (32%). The fishers described 59 target ethnospecies, with eight being common in 90% (n = 9) of the communities under study. These workers use the following fishing gear: line, longline, gillnet, trawl net, and harpoon. Socioenvironmental oceanography enables obtaining basic information on artisanal fishing, which can support the development of public policies for the sector with a view to maintaining this activity in Espírito Santo State.